Possibility of Using Disposable Polymeric Containers in the Production Technology of Live Plague Vaccine - D. A. Sharov; I. V. Darmov; I. V. Kosenkov; A. A. Leshchenko; S. V. Bagin; D. A. Mokhov; A. G. Lazykin; E. A. Kovalenko (Проблемы особо опасных инфекций, 2024)
The aim of the work was to assess the possibility of using disposable polymeric containers in the production technology of the live plague vaccine.Materials and methods. We deployed the vaccine strain Yersinia pestis ЕV NIIEG for the work. A standard disposable 10 L Flexboy type polymeric container manufactured by Sartorius Stedim Biotech, equipped with Sartopore 2 filter capsules, was used for submerged cultivation of plague microbe inoculum. This method was compared to the regulated technology for obtaining seed cultures using glass bottles with a volume of 20 liters. The control of the produced seed cultures of the vaccine strain EV was performed in accordance with FS.3.3.1.0022.15. The cultivation of the seed culture in a disposable polymeric container was carried out in a liquid nutrient medium at a temperature of 26 to 28°C with continuous barbotage and mechanical agitation with a platform oscillation frequency of 80 to 90 per minute. For aeration, compressed air with a pressure of 0.3 to 0.4 kgf/cm2 was used. The volumetric flow rate of sterile air supplied for aeration ranged from 0.9 to 1.0 l/min.Results and discussion. The use of disposable polymeric containers made it possible to reduce the duration of the technological stage of obtaining a seed culture by 1.7 times and increase the yield of live microbes per unit volume of the nutrient medium by 2.8 times, as compared to the regulated production technology. Thus, the possibility and prospects of using disposable polymeric containers in the production technology of live plague vaccine at the stage of preparation of sowing cultures is evidenced.